The media effect on individuals in the cultural transformation of Shekhawati Region: a case study. (2nd August 2019) - Mishra, Anuradha
It is seen that media access influences the opinion formation of an individual, affecting their decision making ability in bringing an attitudinal change leading to a social transformation. In India, the technologically driven media has reached rural parts of the country and seems to be greatly influencing the indigenous culture of Lachhmangarh Village of Shekhawati Region, Rajasthan. To understand the extent of cultural transformation, various factors of culture, i.e., food, lifestyle, art and architecture, costume, music, dance, language and festivals are studied. The study attempts to identify the penetration of media and subsequent positive and negative influence on cultural transformation. It also attempts to analyse efforts undertaken by media and government to preserve the culture. The researcher conducted ethnographic study validating it through method triangulation. 200 respondents' filled questionnaires formed the quantitative data while qualitative data was collected through observation method, in-depth interviews and focused group discussion with 50 respondents each.